MESUDD: towards a multi–lingua expert system for rural m–healthcare. (18th October 2012) - Oladosu, John Babalola; Olamoyegun, Michael Adeyemi
A good number of applications and hardware devices for healthcare services have been produced through research efforts. A key limitation of the existing systems that are implemented for mobile devices, however, is that they have not adequately addressed language barrier, deplorable access to medical practitioners, cost constraints among other challenges peculiar to rural communities in developing and underdeveloped countries. This paper presents one of the solutions developed in our research efforts at addressing some of the aforementioned limitations of the existing systems. The work produced a novel mobile software tool that addresses the provisioning of real–time language translation for illiterate indigenous patients to interact with a medical expert system via a small mobile computing device for diagnoses and drug prescription where there is no doctor. Usability assessment of the tool was conducted by engaging physicians, paramedics and patients. The result of that assessment is presented.